If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3g + 4n = 18 Solving 3g + 4n = 18 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-4n' to each side of the equation. 3g + 4n + -4n = 18 + -4n Combine like terms: 4n + -4n = 0 3g + 0 = 18 + -4n 3g = 18 + -4n Divide each side by '3'. g = 6 + -1.333333333n Simplifying g = 6 + -1.333333333n
| v/8+2 | | 2x+4.1=x+1.1 | | n=9200ln(5(3)+3) | | 5/4x5/3(2+10) | | 2n+8=8 | | 8(x-3)=4x+-8 | | 4x^2-6x-56=3x-16 | | 4/5y-9=-1 | | 4a+3=56 | | 2/2/3x8 | | 15+h=-15 | | 4x-7(x-2)= | | 8x+11/9=-5 | | log(2x-8)-log(6x)=2 | | x^3+10x^2+9x=0 | | 22/3x8 | | 7+9n=79 | | 20x^3+60x^2+25x=0 | | 3x^2+7+8=6 | | c=-5c+-30 | | 3x^2+7+18=6 | | 3/4x-1/3=-8 | | d/-7=-4 | | 2x/6=-10 | | -p^2+p=18 | | 8k-5k=15 | | x^2+56x-406.25=0 | | 3x/9=-9 | | 5X+(-20)=65 | | v=1/3m2h | | -41-3x=9-3x | | 32=h+5 |